DENTAL CARE LEVEL ASSESSMENT AT SDS/TEN: SYSTEMATIC ANALYSIS OF CLINICAL CASES - S.V. Kolomiiets; O.V. Hurzhii; V.I. Shynkevych (Ukrainian Medical Stomatological Academy, 2019)
Background. Dental care is essential for all hospitalized patients with Stevens-Johnson syndrome and/or toxic epidermal necrolysis (SJS/TEN), the clinical cases of which are reported annually in scientific journals. Purpose of publication was analysis of dental care from clinical reports about SJS/TEN and ours own clinical case of SJS, for dental help optimization. Materials and methods. The clinical cases reports in Russian and Ukrainian languages of databases Google and Google Academy from 2016 to May 2019 (and some earlier publications) were selected by the keywords "Stevens-Johnson syndrome", "Lyell's syndrome", "toxic epidermal necrolysis" and analyzed together with our own clinical case of SJS. Clinical case. The list of dental prescriptions, according to the case history, included: local anesthesia with 10% lidocaine spray, rinsing the mouth with a decoction of herbs; later lidocaine was replaced by the metacyl-anesthesin suspension applications. Discussion. Currently there are no clinical guidelines for wound care and skin care of Stevens-Johnson syndrome and toxic epidermal necrolysis. Analysis of the literature and ours own clinical case showed the simultaneous using of the same drugs in different forms. As a rule, this concerned systemic and local corticosteroids, and a combination of at least two antiseptics. Insufficient attention was paid to assessing the periodontal state of patients and to professional and/or individual measures to control dental biofilm (mentioned in only one case). Meanwhile, it can be very important in patients with chronic periodontitis, given the role of periodontal pathogens in dental biofilm as a reservoir in particular for respiratory infections that can lead to nosocomial pneumonia. Using of outdated empirical antiseptics (furatsilin, potassium permanganate, sodium tetraborate, colloid silver) were reported, which toxicity exceeds the useful effect. When the benzocaine anesthetic (the para-aminobenzoic acid ester derivatives group) was selected, cross-reactivity with other sulfonamides, which are known to cause severe hypersensitivity reactions, was not taken into account. There were no reports about non-adhesive modern dressings for affected skin. There was a case of using empirical drugs without evidence base (solcoseryl, trypsin). At present, accumulated evidence suggests the role of endogenous hepatogenic hypervitaminosis A, which leads to the spillage of toxic retinoid compounds into the circulation, and the development of cytotoxicity with the widespread of granulosin-mediated apoptosis. So the use of keratoplasty drugs, rich in carotenoids, in particular sea buckthorn oils, can be harmful. Thus, lately, the methods and means of dental care have not hardly changed, despite the 4th year of the order No. 916 dated 12.30.2015 "Drug allergies, including anaphylaxis" of the Ministry of Health of Ukraine. Conclusions. 1. When treating patients with SJS/ТEN, withdrawal of any agent suspected of causing the condition is critically important. 2. It is necessary to more widely introduce modern non-adhesive dressings on the affected skin, as they require fewer changes and caused less discomfort to the patients. 3. Oral lesions are managed with mouthwashes; topical anesthetics are useful in reducing pain and allowing the patient to take in fluids. This determines the optimal minimum in order to avoid new adverse effects from unjustified empirical and outdated polypharmacy. Perspectives. The clinical guidelines from the order No. 916 dated June 30, 2015, "Drug allergy, including anaphylaxis" of the Ministry of Health of Ukraine should be more widely studied and used in practice, including dentistry.